Desire and Disinterest in Dusklands. - Hayes, Patrick (English in Africa, 2025)
Disinterest is one of the most distrusted of all the terms which pass down to us from post-Kantian aesthetic theory, because it is often taken to imply an ideologically suspect transcendence of the desiring embodied subject. Yet the need to which it points persists, as is evident from Coetzee's essay "Erasmus: Madness and Rivalry" (1992), where a certain conception of aesthetic disinterest (a sought-for 'evasive (non)position inside/outside the play') is seen as being importantly related to, rather than disavowing, the desire of writer and readers alike. This paper traces the prehistory of these significant remarks back to the period of Dusklands, and to Herbert Marcuse's attempt to conjoin Freudian psychoanalysis with post-Kantian aesthetic theory. I will argue that Marcuse was an influence Coetzee needed both to assimilate and to challenge.